Theoretical investigation of energy levels and transitions for Pr iv. Issue 1 (1st September 2022) - Gaigalas, G; Rynkun, P; Banerjee, S; Tanaka, M; Kato, D; Radžiūtė, L
ABSTRACT: We present extensive energy levels (1110 levels) and transition data for the Pr iv . We also show the effect of such atomic data on opacity for neutron star (NS) merger. We performed energy spectra and transition data calculations using the GRASP2018 package, which is based on the multiconfiguration Dirac–Hartree–Fock and relativistic configuration interaction methods. Using the GRASP2018 data, the opacities in the NS merger ejecta containing pure Pr are calculated. Energy levels are compared with recommended values from the NIST Atomic Spectra Database and other available works. Furthermore, electric dipole (E1) transition data, line strengths, weighted oscillator strengths, and transition rates are computed between the above levels. We estimate the uncertainties of the computed line strengths giving the accuracy class. The computed line strengths are also compared with other theoretical computations. We proposed few ways to estimate the uncertainties of the line strengths of the E1 transitions. Our calculation for opacity for a typical condition of NS merger ejecta at t ∼ 1 d shows that the Planck mean opacity of Pr 3 + reaches $\sim 1\, \rm cm^{2}\, g^{-1}$ at $T\, \sim \, 15000$ K. The opacity is higher than that by the previous studies, thanks to the higher completeness of the atomic data. We also highlight the importance of accurate atomic data for the opacity by comparing it with the opacity using the atomic calculation from HULLAC. Moreover, we identify the important configurations, especially for the transitions between the high-lying levels for the opacity of 3 + ionized lanthanides.